Strengthening the Disciplinary Character Education of Santri through Discipline Development in Islamic Boarding Schools - Andi Anirah; Naima Naima; Retoliah Retoliah; Nursyam Nursyam; Erniati Erniati (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
Strengthening disciplinary character education through disciplinary development is an inseparable part of Islamic boarding schools. As traditional Islamic educational institutions, Islamic boarding schools have broader goals than simply transmitting religious knowledge. One of the main goals of Islamic boarding schools is to form an Islamic character in students. Discipline is a means of creating attitudes and behaviors that are contrary to the teachings of the Islamic religion, including obedience, patience, and responsibility. This research aims to find and explain discipline development activities in strengthening character education in Islamic boarding schools. The research method used was descriptive qualitative with a field focus at the Al-Istiqamah Ngatabaru Modern Islamic Boarding School, Central Sulawesi. Data collection methods are carried out through interviews, observation, and documentation. The data analysis method uses data reduction techniques, presentation, verification, and conclusions. The research found that strengthening disciplinary character education and developing disciplinary character were two important activities at the Al-Istiqamah Ngatabaru Modern Islamic Boarding School, South Sulawesi. Through these two activities, the disciplined character of students can be realized to support various religious activities in Islamic boarding schools. From this disciplined character in participating in religious activities, students become individuals who master a lot of religious knowledge and always behave well in everyday life.